2021
DOI: 10.1186/s40623-021-01385-5
|View full text |Cite
|
Sign up to set email alerts
|

Very broadband strain-rate measurements along a submarine fiber-optic cable off Cape Muroto, Nankai subduction zone, Japan

Abstract: Distributed acoustic sensing (DAS) is a new method that measures the strain change along a fiber-optic cable and has emerged as a promising geophysical application across a wide range of research and monitoring. Here we present the results of DAS observations from a submarine cable offshore Cape Muroto, Nankai subduction zone, western Japan. The observed signal amplitude varies widely among the DAS channels, even over short distances of only ~ 100 m, which is likely attributed to the differences in cable-seafl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…However, DAS is sensitive to temperature as well-the combined effects of temperature on the index of refraction and thermal expansion equate to an equivalent elastic strain of 1 nɛ per 10 mK. At seismic frequencies, thermal signals can be neglected (Lindsey et al, 2020), but at tidal frequencies and in submarine environments with significant temperature gradients, temperature effects may dominate the DAS measurement (Ide et al, 2021). Throughout the experiment, observed OSGW amplitudes are on the order of 100 nɛ between 3 and 6 km where the average water depth is about 40 m. This equates to a temperature signal of order 1 K, which is unreasonable given typical stratification and OSGW displacement near the seafloor.…”
Section: The Nature Of the Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DAS is sensitive to temperature as well-the combined effects of temperature on the index of refraction and thermal expansion equate to an equivalent elastic strain of 1 nɛ per 10 mK. At seismic frequencies, thermal signals can be neglected (Lindsey et al, 2020), but at tidal frequencies and in submarine environments with significant temperature gradients, temperature effects may dominate the DAS measurement (Ide et al, 2021). Throughout the experiment, observed OSGW amplitudes are on the order of 100 nɛ between 3 and 6 km where the average water depth is about 40 m. This equates to a temperature signal of order 1 K, which is unreasonable given typical stratification and OSGW displacement near the seafloor.…”
Section: The Nature Of the Measurementmentioning
confidence: 99%
“…In particular, Williams et al (2019) showed that OSGW directional spectra observed with OBDAS exhibited a clear Doppler shift indicating the presence of a current. Lindsey et al ( 2019) also speculated about possible signatures of internal gravity waves and tidal bores, and later Ide et al (2021) reported tidal signals in deep water. Yet, the oceanographic applications of OBDAS remain largely unexplored.…”
mentioning
confidence: 99%
“…The DAS data are recorded by AP Sensing (model N5200 A) over a sensing length of 50 km along the cable, with a gauge length of 40.4 m and a sensor spacing of 5.1 m, and the differential phase at each channel was measured by the interrogator: the differential phase can be converted to strain. Detailed descriptions of the cable and AP Sensing observations can be found in Ide et al (2021) and Matsumoto et al (2021), respectively. Water depth of the cable ranges between 0 and 1,100 m, and topographic relief is present at a cable distance of 30 km from the coastline.…”
Section: Datamentioning
confidence: 99%
“…In recent years, there has been a rapid development of DAS in seismic acquisition. DAS is an optical fiber sensing technology that offers the potential of broadband frequency recording and near-continuous spatial sampling of earth strain and temperature variation signals (Ajo-Franklin et al, 2019;Ide et al, 2021). Its unprecedented spatial sampling could improve the spatial resolution of subsurface seismic images (Ajo-Franklin et al, 2019;Dou et al, 2017;Lellouch et al, 2019;Rodríguez Tribaldos & Ajo-Franklin, 2021;Rodríguez Tribaldos et al, 2021;Spica, Nishida, et al, 2020;Williams et al, 2019).…”
Section: Supporting Informationmentioning
confidence: 99%